SUPERVISI KUNJUNGAN KELAS UNTUK MENINGKATKAN KOMPETENSI PEDAGOGIK GURU SDN CUKIL 01, TENGARAN, KABUPATEN SEMARANG - Astiti Rahayu Argiani; Slameto Slameto (Kelola: Jurnal Manajemen Pendidikan, 2015)
The problems background in the learning process, teacher and pupils are interpedently connected to one another in the learning classroom process, it is because conversation and encounter process occurred. This learning process is not an uncommon issue. The problems are teacher has not finish classroom materials for the learning process, which cause an impact on the learning process’s implementation, teacher has not developed educational learning’s process, and teacher has not mastered today’s technology. Based on those complications, the best solution is implementing classroom’s visits supervision. The problem’s formulation in this study is whether the supervision of classroom visit can improve teacher’s pedagogical competence at Elementary School of Cukil 01, Tengaran. The research’s purpose is to enhance teacher’s pedagogical competence though the classroom visit’s supervision at Elementary School of Cukil 01, Tengaran The research’s type is school action research which is applied through the phase of identification of focus’s areas, data gathering, analyzes and data interpretation, plan’s arranging, and implementation of the action. The research’s subject is ten teachers through interview and also documentary study. The data gathering’s technique used though interview, observation, questionnaire, and also documentary study. The data processing’s techniques are done with data classifying, data presentation and verification. The validity of test data is using data’s triangulation. The research’s result shows two point they are: (1) The implementation of classroom visit’s supervision obtains a maximum score, that is 94% with a very good criteria (AB) and minimum score is 74% with a good criteria (B). Feedback that is performed also given which is showed are mostly positive answers. (2) The teacher’s pedagogical competence obtains a maximum score, that is 88% with very good criteria (AB) and a minimum score is 70% with a good criteria (B).To conclude the research’s result, through the classroom visit’s supervision is able to improve the teacher’s competence at Elementary School of Cukil 01, Tengaran. Suggestions offered, there should be continuity of the classroom visit’s supervision in the school that agree by all teachers to improve the teachers’ competence in the implementation of learning.